The Use of Phytobiotics in Aquaculture and in Fish Processing Industry: An Overview - Alina MOGODAN; Stefan M. PETREA; Ira A. SIMIONOV; Aurelia NICA; Dragos S. CRISTEA; Victor CRISTEA (Communications of International Proceedings, 2020)
Fish can be called as an indispensable animal-source of food in human diet, due to the content of essential nutrients, in fish meat, with high bioavailability that are found in limited quantities in the diet. So, the present study aims to characterize the recent state of the art related to the use of phytobiotics in aquaculture and in fish processing industry. This aim targets to draw future research directions in the area of phytobiotics use for improving the profitability of fish-based sectors (fish production and processing). The effects of phytobiotic administration in fish diet during the period of preservation of fish meat freshness, from the moment of its slaughter, throughout the processing cycle, is a promising research direction. It can be also concluded that the idea of using phytobiotics in aquaculture, having the effect of preserving the freshness of fish meat for a longer period of time, is still an innovative scientific element, fully applicable to industrial fish production.
Keywords: Aquaculture; Phytobiotics; Fish Processing.